Among the Barons - Haddix, Margaret Peterson (New York Simon & Schuster Books for Young Readers, 2003)
In a future world of false identities, government lies, and death threats, Luke feels drawn to the younger brother of the boy whose name Luke has taken.
Sequel to: Among the betrayed.
710L
103072
Keywords: Brothers; Science fiction; Fiction; Juvenile works